PKM Analysis of Accreditation Results as a Basis for Quality Assurance for PAUD in Magelang Regency - Irma Yuliantina; Arrumaisha; Eka Wartani; Himmatul Jazriyah; Tanti Kartikasari; Wiwiek Sumayni (Jurnal Pengabdian Masyarakat Formosa, 2024)
Community Service in collaboration with the District Education Office. Magelang aims to carry out an analysis of the results of PAUD accreditation which is carried out to determine the strengths and weaknesses of PAUD implementation. Based on the results of this analysis, it is hoped that PAUD managers can develop a comprehensive quality assurance program. Preparation is carried out by analyzing the results of the accreditation findings for each accredited educational unit. The implementation was carried out using the lecture method, namely presentation techniques, followed by a question and answer discussion and preparation of a Follow-up Plan as a form of Technical Guidance activity. Activity evaluation is carried out for each stage by collecting and summarizing data from each activity stage. The results of each unit's Bimtek activities create an RTL to improve service quality and improvements are carried out in accordance with the technical guidance carried out.